S1RS: An inventive abstract art composition developed through the analysis of seafarer and Renjana with a comprehension of the gestalt principle/ Zuriati Mohamed Shaari ... [et al.] - Mohamed Shaari, Zuriati; Wan Mohamad Daud, Wan Samiati Andriana; Mohamed Amin, Noor Hidawati; Abdul Jalil, Farif; Abu Bakar, Rasfan; Mohd Ghazali, Fariz Azmir (Universiti Teknologi MARA, Perak, 2024)
This study pertains to the abstract paintings of two artists who are currently establishing themselves as significant figures in the field of fine art. The artworks are from their most recent solo exhibition, which was held in 2023. Rasfan Abu Bakar's Seafarer is situated at Balai Seni Melaka, while Farif Abdul Jalil's Renjana was held at Segaris Gallery, Publika. The research is structured according to Wallas' theory, which outlines the four stages of creativity: i) preparation, ii) incubation, iii) illumination, and iv) verification. The analysis is predicated on three Gestalt Principles: proximity, closure, and symmetry. A composition template for abstract paintings, known as S1RS, has been developed based on the results of the study's analysis. This template is intended for those who have recently begun to create abstract paintings. In addition, this template has been utilized by researchers to develop an abstract painting that resulted for both balanced and visually appealing.